Analisis Penetapan Beban Kerja Guru BK di Kota Palembang - Syska Purnama Sari; Januar Eko Aryansah (Manajemen Pendidikan, 2020)
The success of an educational institution integrates the performance of each individual conducting organizational activity. Guidance and counseling are part of the activities that are running in the educational institutions. Legally there are some regulations governing workload assignments for school counselors, but in reality the many divisions of assignments given to school counselors are disproportionate. This research aims to present data and factual analysis of workload assignment for school counselors in Palembang. Research using quantitative design, with survey method, to 20 school counsellors in MGBK Palembang. The results showed that 70% of school counsellors gained equal 24-hour students ' equivalence to the national regulation. But in the provision of assignments, school counselors are much busy with administrative affairs. Therefore, coordination and consultation functions between school counselors, school principals, and supervisors need to be addressed in order to provide the main tasks and functions of school counselors more optimally in serving the students and in accordance with the central government policy contained in the Ministry regulations.